PODE A PRODUÇO DE FORÇA SER AFETADA PELA FACILITAÇO NEUROMUSCULAR PROPRIOCEPTIVA, LIBERAÇO MIOFASCIAL, OU AS TAREFAS COMBINADAS? UM ESTUDO CONCORRENTE CONTROLADO E RANDOMIZADO. (CIPEEX, 2022)
ABSTRACTTHE AIM OF THE STUDY WAS TO EVALUATE THE ACUTE EFFECTS OF SETS OF PNF, MYOFASCIAL RELEASE (MLF), OR THE SUM OF THE METHODS, ON STRENGTH DEVELOPMENT. PARTICIPANTS WERE 8 ADULTS WHO RESPONDED TO THE INFORMED CONSENT AND CAME TO THE LABORATORY IN 7 VISITS. THE FIRST VISIT CONSISTED OF A CHARACTERIZATION OF THE SAMPLE. ON THE SECOND AND THIRD VISITS, THE PARTICIPANTS PERFORMED THE DEADLIFT MAXIMUM REPETITION PROCEDURE. FROM THE FOURTH TO THE SEVENTH VISITS, THEY WERE RANDOMLY DIVIDED INTO: A) CTL; B) PNF; C) LMF; D) FNP+LMF. ALL SESSIONS WERE FOLLOWED BY THREE SETS OF DEADLIFT EXERCISES WITH 80% RM. RESULTS: THE REPEATED MEASURES ANOVA SHOWED SIGNIFICANT DIFFERENCES BETWEEN THE CONTROL CONDITION (NO INTERVENTION) AND THE PNF INTERVENTION (P = 0.034) AND LMF+PNF (P = 0.047). HOWEVER, THE CONTROL VS. LMF THERE WERE NO SIGNIFICANT DIFFERENCES (P = 0.07), AS WELL AS PNF VS. LMF (P = 0.585), AND PNF VS. PNF+LMF (P=0.382). CONCLUSION: STRENGTH PERFORMANCE WAS INFLUENCED BY THE PNF METHOD, OR ASSOCIATED WITH LMF, BOTH REDUCING TOTAL WORK.&NBSP;KEYWORDS: STRETCHING. MYOFASCIAL RELEASE. REPETITION MAXIMUM.&NBSP;